The imperative of a Riba-free inclusive financial system - Adeyemi, Adewale Abideen; Muhammad Bashir, Yusuf; Mikail, Said Adekunle; Ibrahim, Mekhlafi; Mustafa, Daud (2011)
Introduction: The relative importance of an efficient and inclusive financial system cannot be ignored. Such system is needed for ensuring efficient allocation of resources, prevention of inequalities in outcome and opportunities especially among the poor micro-entrepreneurs (Demirguc-Kunt, Beck, and Honohan, 2008). According to Chowdhury, Ghosh, and Wright (2005), evidences abound that the financial repressions from both the formal and informal sources of finance interact with many other economic, social and demographic factors to cause the vicious circle of poverty. Based on individual and social characteristics, Demirguc-Kunt, Klapper and Panos (2007:27) suggest that financial constraint is crucial both in promoting entry into self-employment and its subsequent success.